A 2D dislocation dynamic approach to simulating dimensional change in irradiated graphite using anisotropic strain theory. Issue 1 (5th December 2012) - Young, Philippa; Sheehan, Glen; Boone, James; Heggie, Malcolm I.
Abstract A program using two‐dimensional dislocation dynamics with anisotropic strain equations has been written to simulate the dimensional change and stored elastic energy of irradiated graphite. A dislocation based model is put forward as a vehicle for both the longstanding atomic displacement model for dimensional change in irradiated graphite and a new model based on basal slip. As expected the introduction of prismatic dislocation loops (climb dipoles in 2D) results in the expansion of the graphite crystal in the c‐axis direction. Interestingly the stored elastic energy of the system was found to increase with number of dislocation dipoles and reached a maximum at the density which Burakovsky et al. (Phys. Rev. B 61, 15011–15018 (2000) [1]) predicted for melting. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)